Some state-legal problems of overcoming environmental crisis in globalisation era - Гетьман, А. П.; Лозо В. I. (Problems of legality, 2013)
A range of the state-legal problems urgent for overcoming of environmental crisis. The anthropocentric approach is subject to replacement with an ecological imperative with legal maintenance of profitability of environmental management. The aim of the law is to establish conditions of "rent" of a planet with comfort for mankind within sustainable development of natural balance. EU environmental programs are quite successful. Ukraine, joining the eurointegration course, can cooperate with partners in formation of alternative model of development.